2022
DOI: 10.1109/ted.2021.3138360
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Operation and Solder Reflow Compatibility in BEOL-Integrated 16-kb HfO2: Si-Based 1T-1C FeRAM Arrays

Abstract: 16kbit 1T-1C FeRAM arrays are demonstrated at 130nm node with TiN/HfO2:Si/TiN ferroelectric capacitors integrated in the Back-End-of-Line (BEOL). 0 state and 1 state distributions measured on the arrays demonstrate perfect yield at 4.8V operation, with extrapolations suggesting memory window is still open at 6 sigma statistics. Programming speed down to 4ns at 4V is highlighted at the array level, together with endurance up to 10 7 cycles. Promising data retention up to 10 4 s at 125°C is measured on the array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Additionally, gate last FeFET with improved endurance and retention by reduced charge trapping were realized 27 . Furthermore, the first fully integrated functional capacitor‐based ferroelectric random‐access memory (FeRAM) devices were recently demonstrated 28,29 . Ferroelectric tunnel junctions (FTJs) having a tunneling electroresistance controlled by the spontaneous polarization of fluorite‐structured ferroelectrics were also demonstrated as a variant of memristive devices 30 .…”
Section: Advantages and Challenges Of Fluorite‐structured Ferroelectr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, gate last FeFET with improved endurance and retention by reduced charge trapping were realized 27 . Furthermore, the first fully integrated functional capacitor‐based ferroelectric random‐access memory (FeRAM) devices were recently demonstrated 28,29 . Ferroelectric tunnel junctions (FTJs) having a tunneling electroresistance controlled by the spontaneous polarization of fluorite‐structured ferroelectrics were also demonstrated as a variant of memristive devices 30 .…”
Section: Advantages and Challenges Of Fluorite‐structured Ferroelectr...mentioning
confidence: 99%
“…27 Furthermore, the first fully integrated functional capacitor-based ferroelectric random-access memory (FeRAM) devices were recently demonstrated. 28,29 Ferroelectric tunnel junctions (FTJs) having a tunneling electroresistance controlled by the spontaneous polarization of fluorite-structured ferroelectrics were also demonstrated as a variant of memristive devices. 30 In 2020, it was suggested that the robust ferroelectricity of (Hf,Zr)O 2 can be retained even when the film thickness decreases to 1 or 1.5 nm, and it was further suggested that unit-cell-scale information storage would theoretically be possible because of the flat phonon band of ferroelectric HfO 2 .…”
Section: Advantages and Challenges Of Fluorite-structured Ferroelectr...mentioning
confidence: 99%
“…Uwe Schroeder,* Terence Mittmann,* Monica Materano, Patrick D. Lomenzo, Patrick Edgington, Young H. Lee, Meshari Alotaibi, Anthony R. West, Thomas Mikolajick, Alfred Kersch, and Jacob L. Jones DOI: 10.1002/aelm.202200265 ductor devices like ferroelectric capacitors, transistors, and tunnel junctions in recent years. Capacitor-based ferroelectric random access memory [2,3] and ferroelectric field effect transistors [4] using HfO 2based ferroelectrics have already been integrated into state of the art CMOS processes to prove the potential of this new ferroelectric material system. However, a detailed understanding of the ferroelectric phase formation process, including phase transitions, is necessary for continued development because such phase transitions determine ferroelectric device temperature stability.…”
Section: Temperature-dependent Phase Transitions In Hf X Zr 1-x O 2 M...mentioning
confidence: 99%
“…However, a detailed understanding of the ferroelectric phase formation process, including phase transitions, is necessary for continued development because such phase transitions determine ferroelectric device temperature stability. Several phases were reported to be present or coexisting in doped HfO 2 or ZrO 2 films ranging from monoclinic (space group P2 1 /c), tetragonal (P4 2 /nmc), cubic ( 3 Fm m ), rhombohedral (R3m), and different orthorhombic phases that can be nonpolar (Pnma), antipolar (Pbca), nonpolar (Pbca), or polar (Pca2 1 ). [5,6] A remarkable property of the material is the phase coexistence between the nonpolar tetragonal and polar orthorhombic phase.…”
Section: Temperature-dependent Phase Transitions In Hf X Zr 1-x O 2 M...mentioning
confidence: 99%
“…Doped-HfO 2 Ferroelectric Materials. Since the discovery of ferroelectricity in doped-HfO 2 films in 2011 [20], ferroelectric field-effect transistors (FeFETs) and ferroelectric random access memory (FeRAM) have received significant attention [21][22][23][24][25]. Polycrystalline doped-HfO 2 films are considered as promising gate-oxide materials owing to their excellent ferroelectric properties as well as high compatibility with the ultrascale CMOS process.…”
Section: Emerging Ferroelectric Materialsmentioning
confidence: 99%